ANALYSIS OF THE EFFECT OF LONG WORK AND HUMAN RESOURCES TRAINING ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL CULTURE AS INTERVENING VARIABLE AT HAIR GARDEN PT. PERKEBUNAN NUSANTARA III - Fajar Rezeki Ananda Lubis (Institute of Computer Science (IOCS), 2022)
This research aims to analyze the influence of competence and human resource training on employee performance with organizational culture as an intervening variable at Rambutan Perkebunans at PT. Perkebunan Nusantara III. To answer this problem, we conducted research on 100 employees of Kebun Rambutan through a survey approach. The method used is descriptive (narrative) method and multiple linear regression with the formula Z = + 1x1 + 2x2 + Y. The data used are primary data through interview method by filling out questionnaires and secondary data through documentation study. The results showed that the variables of Competence and HR Training simultaneously had a positive and significant effect on Organizational Culture. The variables of HR training and organizational culture simultaneously have a positive and significant effect on employee performance. Meanwhile, competence has a positive but not significant effect on employee performance at Kebun Rambutan PT. Perkebunan Nusantara III. Variables Competence and HR Training through Organizational Culture simultaneously have a positive and significant effect on Employee Performance at Kebun Rambutan PT. Perkebunan Nusantara III.